Regulation on transportation of dangerous good by sea in Malaysia: whether it conforms to international standard / Muhammad Khairil Khalid - Khalid, Muhammad Khairil; Zakaria, Noor Amira; Raduan, Muhammad Rahimi; Burhanuldin, Al-Afiq (2011)
This study, "Regulation on Transportation of Dangerous Good by Sea in Malaysia: Whether it conforms to International Standard" is completed as a fulfilment of the course of Bachelor of Legal Studies (Hons). This study mainly conducted in Shah Alam and Kuala Lumpur to look into the regulations which govern the transportation of dangerous goods in Malaysia. There were.several methods used in order to find answers and to collect facts to answer the research questions and to meet the objectives of the study. Qualitative research which is library - based was conducted to gather information and relevant data for this study. The relevant data was gathered from various text books, journals, articles and internet. The researchers have also conducted several interviews with few respective people in gaining more information such as Dr. Irwin Ooi Ui Joo, Senior Research Fellow, Malaysia Institute for Transport (MITRANS) and last but not least, representatives from Maritime Institute of Malaysia (MIMA), Amy Aai Sheau Ye, Melda Marissa bt. Malek, and Elvia Cory Abu Hasan. These interviews were conducted to provide the researches with a clearer insight of the current situation of the research topic from the point of view of expertise. Apart from that, the researchers have also studied the regulation of transportation of dangerous goods in other countries for the purpose of comparison in the law from another point of view. Overall, it is found that there is not specific law which govern transportation dangerous goods by sea. However, practice on shipping of dangerous goods in Malaysia is guide by international guideline such as International Maritime Dangerous Goods Code (IMDG) Code.